Islamic sukuk as a tool to finance deficit public treasury of Algeria - REMITTA, Habiba (Milev Journal of Research and Studies, 2022)
Public budget deficit causes countries to constantly look for new financing sources to fulfill their financial needs. Among these sources are Islamic Sukuk which represent Islamic financing instruments that has emerged in recent years more importantly after the 2008 global financial crisis, and are used to finance various areas including countries' Budget deficit. Amid Algeria's pursuit to find new funding sources in order to cover the Public Treasury deficit; this research has been carried out to clarify the extent possibility of the accreditation on the sukuk as tools to finance the deficit and consequently to the importance of the role that they play.